The Dynamics of Imagination and Curiosity as a Moral Learning Space for the Character Karima in the Tea Secret Comic, a Study by Maria Nikolajeva - Fitriani, Rahmania Alya; Indriyani, Jiphie Gilia (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
This study analyzes the character development of Karima in the comic Tea Secret: Teka-Teki Tumpukan Jerami by Ulya Amara Putri using Maria Nikolajeva’s theory of children’s character development. The focus lies in how the world is perceived by the child character and how the narrative context reflects children’s learning and psychological growth. Using a qualitative method with a cognitive aesthetic approach, this research examines the transformation of the protagonist’s subjectivity. The analysis demonstrates that Karima undergoes a significant transformation from a passive, innocent, and doubtful child to a braver, more confident, and reflective individual through social interactions with her peers. The symbol of the fragrant haystack represents the process of understanding the unknown through logic and empathy. This study concludes that the Tea Secret comic functions as a mirror of growth that instills moral values such as bravery, solidarity, and responsibility, while proving the psychological depth of popular Indonesian children’s literature.